An Analysis on Translation Method and Quality of Passive Voice in I Am Number Four Novel by Nur Aini - INDAH PRASMAWATI, MARATINA (2016)
This research focuses on analyzing the passive voices found in I Am Number Four novel and its translation. The objectives are to identify the translation method of passive voice applied in I Am Number Four novel, to describe the accuracy of passive voice translation in I Am Number Four novel, to describe the readability of passive voice translation in I Am Number Four novel, and to describe the acceptability of passive voice translation in I Am Number Four novel. This research applies descriptive qualitative method. The data are the passive voices found in I Am Number Four novel and its translation. The data sources are the novel entitled I Am Number Four by Pittacus Lore in 2010 and its translation by Nur Aini in 2011, and the informant. The ways to collect data are by using documentation, questionnaire and in-depth-interview. The results of the research show that, firstly, there are six methods applied to the translation namely word-for-word translation, literal translation, faithful translation, free translation, idiomatic translation and communicative translation. From 116 data of passive voice in I Am Number Four novel, there is 1 or 0.9% datum belongs to word-for-word translation, there are 46 or 39.6% data belong to literal translation, there is 1 or 0.9% datum belongs to faithful translation, there are 6 or 5.2% data belong to free translation, there are 7 or 6% data belong to idiomatic translation, and there are 55 or 47.4% data belong to communicative translation. It shows that the most dominant method which is used by the translator is communicative translation that there are 55 or 47.4% data from 116 data of passive voice in I Am Number Four novel. Secondly, the quality of translation is influenced by three factors namely accuracy, readability and acceptability. From 116 analyzed data of passive voice found in I Am Number Four novel, there are 111 or 95.7% data belongs to accurate translation and 5 or 4.3% data belong to less accurate translation. So, the accurate translation is higher than less accurate translation which means I Am Number Four novel has good accuracy. Thirdly, From 116 analyzed data of passive voice found in I Am Number Four novel above, there are 109 or 94% data belong to readable translation and 7 or 6% data belong to less readable translation. So, the readable translation is higher than less readable translation which means I Am Number Four novel has good readability. The last, from 116 analyzed data of passive voice found in I Am Number Four novel above, there are 115 or 99.1% data belong to acceptable translation and 1 or 0.9% datum belongs to less acceptable translation. So, the acceptable translation is higher than less acceptable translation which means almost all the data of passive voice found in I Am Number Four novel has good acceptability.